Influence of hypovolemic and hypertonic treatments on plasma vasopressin levels and fluid balance in the thyroidectomy-induced hypothyroid rats - Mogulkoç, Rasim; Dogru, Osman; Baltaci, A. Kasim; Yilmaz, Bayram; Kelestimur, Haluk (Maghira and Maas Publications, 2000)
OBJECTIVES: This study was undertaken to investigate the effects of hypovolemic and hypertonic treatments on plasma vasopressin (AVP) levels and fluid balance in thyroidectomy-induced hypothyroidism in the rat. The influence of hypothyroidism on AVP responsiveness to hypertonic and hypovolemic stimuli were compared. MATERIALS AND METHODS: Adult male rats were divided into two groups. The rats were surgically thyroidectomized (hypothyroid) or sham-operated (euthyroid). Two weeks later these groups were further divided in three subgroups each containing six rats. The first subgroup consisted of unchallenged rats. The second group underwent hypovolemic treatment by using I.P. 700 mg polyethylene glycol. The third subgroup consisted of hypertonic (1.5 M NaCl; 1 ml/100 g) stimulated animals. All rats were decapitated and trunk blood collected in heparinized tubes. Plasma samples were stored at -20°C until assayed. Plasma AVP T3 and T4 levels were measured by radioimmunoassay. Hematocrit values and plasma Na and K concentrations were also determined. RESULTS: In the hypothyroid rats, hypovolemic treatment significantly reduced the expected increases in plasma AVP levels (p < 0.05) compared to the respective intact animals. In the hypertonic group, similar increases occurred in plasma AVP levels of hypothyroid and euthyroid rats. Hematocrit values and plasma Na concentrations were not significantly different in the hypothyroid rats compared to euthyroid rats. CONCLUSION: In conclusion, thyroidectomy-induced hypothyroidism may affect AVP response to hypovolemic stimulus although it has no important effect on basal AVP levels nor AVP response to hypertonic stimulus.
Keywords: Fluid balance; Hypothyroidism; Rat; Thyroidectomy; Vasopressin